EFFECT OF ROTATION SPEED OF RBC ON SUGAR WASTE WATER TREATMENT - Ali, Munawar; Safirin, MT (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Sugar Industry waste water has a high Chemical Oxygen Demand (COD) content so that it becomes a serious threat to the environment if it is not treated properly. For this reason, it is necessary to carry out processing efforts, one of which is with an alternative processing technology using a Rotating Biological Contactor (RBC). RBC is a wastewater treatment reactor physically and biologically consisting of a circular disk rotated by a shaft at a certain speed. This study aims to determine the efficiency of removal in treating wastewater from sugar factories and to identify microorganisms that play a role in the process of removing organic matter. In this study using variations of disc rotation speed and influent COD concentration. The parameter studied was COD from the sugar factory wastewater from Candi Baru, Sidoarjo. The results of the most effective variations in COD removal were at a disc rotation speed of 4 rpm with an influent COD concentration of 260 mg/L and for parameters. The highest reduction efficiency is 87.69 % for COD. The overall results of this study indicate that changes in disc rotational speed affect the removal efficiency for the COD parameter.